MALAT1 rs619586 as a potential genetic marker of pituitary adenoma susceptibility and aggressiveness - Juskiene, Martyna; Duseikaite-Vidike, Monika; Vilkeviciute, Alvita; Baikstiene, Ieva; Makstiene, Jurgita; Poskiene, Lina; Tamasauskas, Arimantas; Verkauskiene, Rasa; Liutkeviciene, Rasa; Zilaitiene, Birute (Frontiers in Endocrinology, 2026)
BackgroundPituitary adenomas are slow-growing tumors that originate from the anterior part of the pituitary gland. These tumors are associated with dysregulation of a number of long non-coding RNAs (lncRNAs). Metastasis-associated lung adenocarcinoma transcript-1 (MALAT-1) is a long non-coding RNA (lncRNA) that has been implicated in the regulation of cell proliferation, gene expression, apoptosis, differentiation, and cell cycle transition in various tumors, including pituitary adenomas (PA).ObjectiveTo evaluate the impact of MALAT1 gene variants (rs3200401, rs619586, and rs1194338) and immunohistochemical markers (Ki-67 and p53) on the susceptibility and clinical characteristics of PA.Methodsa case-control study included patients with PA and age- and gender-matched controls. PA diagnosis was confirmed through MRI/CT imaging and/or histopathological examination. DNA was extracted from peripheral blood samples, and three MALAT1 variants (rs3200401, rs619586, and rs1194338) were genotyped using TaqMan® real-time PCR. The expression of Ki-67 and p53 were evaluated immunohistochemically using digital image analysis. Statistical analyses included chi-square tests to compare genotype and allele distributions, logistic regression to estimate PA risk (odds ratios, 95% confidence intervals), and nonparametric tests for biomarker evaluation.ResultsAmong 390 participants (145 PA and 245 controls), only the MALAT1 rs619586 variant showed statistically significant associations after Bonferroni correction (p < 0.016). The rs619586 G allele was more frequent in PA patients than in controls (4.1% vs. 0.8%, p = 0.001) and increased the odds of developing PA by 4.1-fold under the additive model (OR = 4.139, 95% CI: 1.365- 12.551, p = 0.012). The G allele remained significantly associated across several clinical subgroups, including microadenomas, macroadenomas, invasive PAs, and PAs with recurrence (p ≤ 0.015). In PA tissues, p53 H-scores were higher in macroadenomas compared with microadenomas (p = 0.047), and patients with the rs619586 AA genotype showed significantly higher p53 expression than those with the AG genotype (p = 0.008). A moderate positive correlation was observed between Ki-67 LI and p53 expression (ρ = 0.268, p = 0.035).ConclusionsMALAT1 rs619586 G allele is significantly associated with an increased risk of PA and its more aggressive clinical features, including invasiveness and recurrence. These findings suggest that rs619586 may serve as a potential genetic marker linked to PA susceptibility. Additionally, the observed relationship between p53 expression and tumor proliferation highlights its potential role in PA tumorigenesis. Further studies are needed to confirm these associations and clarify the underlying molecular mechanisms.